The impact of COVID-19 perceived threat and restrictive measures on mental health in Italy, Spain, New York, and Hong Kong: An international multisite study - Vagnini, Denise; Hou, Wai Kai; Hougen, Clint; Cano, Adrián; Bonanomi, Andrea; Facchin, Federica; Molgora, Sara; Pagnini, Francesco; Saita, Emanuela (Frontiers in Psychology, 2022)
In the early stages of the COVID-19 pandemic, Italy, Spain, New York, and Hong Kong stood out for the high rate of infections. Given this scenario, a web-based international multisite and cross-sectional study was conducted between April and May 2020 to investigate the psychological impact of the pandemic and the restrictions imposed by the governments in these countries. We expected similar patterns in European countries, and no significant differences in terms of psychological impairment between Hong Kong (subjected to restrictions for a longer time, but with a previous experience related to SARS) and the other areas. Participants were 1955 adults from the above-mentioned areas. We assessed anxiety (GAD-7), depression (PHQ-9), COVID-19-related threats, and perceived burden of restrictive measures. Two-explorative factor analyses with Promax rotation identified COVID-19-related factors: personal physical threat; personal economic threat; global economic threat; and restriction-related burden. ANOVAs studied locations’ differences; and two-separate hierarchical multiple regression analyses by location determined whether and how COVID-19-related variables were associated with anxiety and depression, adjusting for age and sex. Italy and Hong Kong showed higher anxiety than Spain(p<0.05); Hong Kong scored higher on depression than Italy and Spain(p<0.001), which highlighted the lowest mean-score. New York participants showed the poorest mental health conditions. Anxiety was predicted by restriction-related burden (βNY=0.242; βHK=0.116) and personal economic threat (βNY=0.246; βHK=0.145) in New York (Adj.R2=0.125) and Hong Kong (Adj.R2=0.079); by global economic threat (β=0.199) and restriction-related burden (β=0.124) in Italy (Adj.R2=0.108); and by personal physical threat (β=0.144) in Spain (Adj.R2=0.049). Depression was predicted by restriction-related burden (βNY=0.313; βHK=0.120), and personal economic threat (βNY=0.229; βHK=0.204) in New York (Adj.R2=0.161) and Hong Kong (Adj.R2=0.089); by global economic threat (β=0.209) in Italy (Adj.R2=0.149); and no predictors emerged in Spain. Findings could contribute to understand the specific impact of the pandemic on people’s psychological health in each area, along with the factors that impacted mental health. This information may be useful to implement prevention interventions in case of restrictions.